MY SAY: Priming a third-generation Alliance - Abd Razak, Dzulkifli (2010)
Much has been said about the Alliance or Perikatan as a political entity, and later Barisan Nasional (BN) as a pre-election pact, that dominated the Malayan-Malaysian scene even before independence was won. This is uniquely Malaysian, given that in most cases one hears of pacts after an electoral process, where political parties scramble to form a government with a comfortable majority. The most recent cases were in the UK and Australia.